Pendidikan Seks Bagi Siswa di Masa Pandemi : Apa yang dilakukan Guru Bimbingan Konseling di Sekolah Menengah? - Ruri Anita Lessy; Amirah Diniaty (Institut Agama Islam Negeri Kerinci, Indonesia, 2022)
This research aimed at knowing 1) the role of guidance and counseling teachers in providing sex education to students during the pandemic and 2) supporting and obstructing factors in the successful implementation of counseling services regarding sex education at State Senior High School in Pekanbaru. It was a case study approach. The primary informants of this research were four guidance and counseling teachers and ten students. The object of this research was the role of guidance and counseling teachers in providing sex education to students during the pandemic period. Interview and documentation techniques were used for collecting the data. Data analysis using data reduction, data presentation, and conclusion. The findings of this research showed that guidance and counseling teachers experience obstacles in providing sex education, this is due to time constraints. Students stated that they needed guidance from the guidance and counseling teachers in understanding sex education. On the other hand, guidance and counseling teachers did not play active roles in providing sex education to students during the pandemic; this is due to limited time. The supporting factors in implementing sex education services were the experience of guidance and counseling teachers, collaboration with various parties, facilities and infrastructure, and exciting material. The obstructing factors in implementing sex education services were the educational background of guidance and counseling teachers, the pandemic and limited time, the lack of students' interest to consult, the student's personalities and desire to change, and the use of media, the views on sex education that was taboo and also the use of proper grammar. The findings of this research suggested that special attention was needed from guidance and counseling teachers and parents in guiding students to understand sex education.